Cover Feature: Structure Elucidation of Lithium Compounds Using 7Li Residual Quadrupolar Couplings (Chem. Eur. J. 23/2023). Issue 23 (27th March 2023) - Rüttger, Franziska; Patten, Tim; Kretsch, Johannes; Krawczuk, Anna; Stalke, Dietmar; John, Michael
Abstract : Shedding light on the structure and solvation state of lithium compounds in aligned solution: The residual quadrupolar coupling of 7 Li in a range of lithium complexes due to the interaction of the electric field gradient (shown in its graphical tensor form) with the alignment in a stretched polymer gel has been investigated using NMR spectroscopy. The preferred orientation of the molecules in the anisotropic environment is illustrated in the background. More information can be found in the Research Article by M. John and co‐workers (DOI: 10.1002/chem.202203995 ).